A perovskite solar cell based on 1,3-benzenedithiol self-assembled monolayer modified copper electrode and a preparation method thereof

CN122892371APending Publication Date: 2026-10-09INST OF MATERIALS HENAN ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610999671.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]针对现有技术中铜电极存在的能级失配、易迁移和稳定性差的问题,本发明提供了一种基于1,3-苯二硫酚自组装单分子层修饰铜电极的钙钛矿太阳能电池及其制备方法,采用1,3-苯二硫酚(BDT)对铜电极进行界面修饰,1,3-苯二硫酚一方面能够调控铜的费米能级、降低铜的氧化电位,解决纯铜电极能级失配问题,另一方面,1,3-苯二硫酚分子中的-SH基团与铜表面形成Cu-S共价键,在铜电极内侧形成连续、致密的保护层,有效抑制铜的氧化及迁移,从而提升器件的稳定性

Benefits of technology

本发明采用有机分子1,3-苯二硫酚作为自组装单分子层,对替代贵金属金电极的低成本金属铜进行界面修饰,同步调控铜的费米能级。该方法不仅有效抑制了铜的氧化、碘腐蚀及金属/卤素离子的双向迁移,还同时解决了纯铜电极的能级失配、易迁移和稳定性差的问题,从而在显著降低电极材料成本的前提下,实现了钙钛矿太阳能电池的高效率、高稳定性与低成本化的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122892371A_ABST
    Figure CN122892371A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite solar cell based on 1,3-benzenedithiol self-assembled monolayer modified copper electrode and a preparation method thereof. The cell comprises a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a back electrode layer which are sequentially stacked from bottom to top. A 1,3-benzenedithiol self-assembled monolayer is arranged between the hole transport layer and the back electrode layer. The back electrode is a copper electrode. The 1,3-benzenedithiol molecules are anchored inside the copper electrode through Cu-S covalent bonds formed by the -SH groups of the 1,3-benzenedithiol molecules and the copper surface, forming a continuous and dense self-assembled monolayer. The self-assembled monolayer can effectively regulate the Fermi level of copper, eliminate the Schottky barrier between the hole transport layer and the copper electrode, and inhibit the oxidation of copper, iodine corrosion and the bidirectional migration of metal / halogen ions. The application replaces the noble metal gold with low-cost copper as the electrode, significantly reduces the material cost while ensuring the photoelectric conversion efficiency, and improves the stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite solar cell technology, specifically to a perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer and its preparation method. Background Technology

[0002] Perovskite solar cells (PSCs) are widely recognized as one of the most promising next-generation photovoltaic technologies due to their high power output and excellent photoelectric conversion efficiency. However, the selection of electrode materials remains a core bottleneck in their commercialization process.

[0003] Currently, most PSCs use gold or silver as the back electrode. Au electrodes are extremely expensive, accounting for over 75% of the total material cost of the device, severely limiting their large-scale application. While Ag electrodes are relatively inexpensive, they readily diffuse with iodine ions in the perovskite layer, forming insulating AgI at the interface, leading to rapid performance degradation. Therefore, significantly reducing electrode costs while maintaining high efficiency and long-term stability is a key challenge for the commercialization of PSCs.

[0004] To address this challenge, abundant and inexpensive copper has attracted widespread attention. Copper's conductivity and work function are similar to gold and silver, making it an ideal candidate material to replace noble metal electrodes. Research indicates that Cu is a highly promising electrode material for long-life, low-cost perovskite solar cells, suitable for long-term operation. However, in practical applications, pure copper electrodes themselves still present three major problems: (1) Fermi level mismatch, a large Schottky barrier is formed between copper and hole transport layer (HTL), which hinders the effective extraction of holes; (2) Copper ions have high electrochemical migration activity and easily diffuse into the interior of the perovskite layer to form deep energy level defects. At the same time, iodine ions in the perovskite will also migrate to the electrode and react to generate CuI. (3) Copper is easily oxidized when exposed to air or trace amounts of moisture.

[0005] These problems ultimately lead to low device efficiency and poor stability.

[0006] To address the aforementioned challenges, researchers have developed various strategies, including composite electrodes and interface modulation. Reference 1, "LIN C, NGIAM J, XU B, et al. Enhancing the Operational Stability of Unencapsulated Perovskite Solar Cells through Cu-Ag Bilayer Electrode Incorporation. Journal of Materials Chemistry A, 2020, 8: 8684-8691," employs a Cu / Ag composite top electrode, utilizing the synergistic effect of Cu and Ag to simultaneously suppress AgI formation and Cu oxidation, significantly improving the operational stability of unencapsulated devices. Reference 2, “XU Z, LIN, NIU X, et al. Balancing Energy-Level Difference for Efficient ni-pPerovskite Solar Cells with Cu Electrode. Energy Mater Advances, 2022,” proposes an “energy level difference balancing” interface control strategy. By synergistically matching the energy levels of the perovskite, HTL, and Cu interfaces through a Spiro-OMeTAD / PTAA composite hole transport layer, the interface energy difference of the Cu electrode nip-type cell is optimized. The results show that the perovskite / HTL energy level difference is 0.32 eV and the HTL / Cu energy level difference is 0.30 eV, achieving efficient carrier extraction and transport. Summary of the Invention

[0007] To address the problems of energy level mismatch, easy migration, and poor stability of copper electrodes in existing technologies, this invention provides a perovskite solar cell based on a copper electrode modified with a self-assembled monolayer of 1,3-benzenedithiophenol and its preparation method. 1,3-benzenedithiophenol (BDT) is used to modify the interface of the copper electrode. On the one hand, 1,3-benzenedithiophenol can regulate the Fermi level of copper and reduce its oxidation potential, solving the energy level mismatch problem of pure copper electrodes. On the other hand, the -SH groups in the 1,3-benzenedithiophenol molecule form Cu-S covalent bonds with the copper surface, forming a continuous and dense protective layer inside the copper electrode, effectively inhibiting copper oxidation and migration, thereby improving the stability of the device.

[0008] The technical solution provided by this invention is as follows: In a first aspect, the present invention provides a perovskite solar cell based on a copper electrode modified with a 1,3-benzyldithiophenol self-assembled monolayer, comprising a transparent conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer and a back electrode layer stacked sequentially from bottom to top, wherein a 1,3-benzyldithiophenol self-assembled monolayer is further disposed between the hole transport layer and the back electrode layer.

[0009] Furthermore, the back electrode is a copper electrode, and the thickness of the back electrode layer is 140-160 nm.

[0010] Furthermore, the perovskite light-absorbing layer comprises a PbI2 layer and a FAI-MACl layer stacked sequentially from bottom to top.

[0011] Furthermore, the transparent conductive substrate is indium tin oxide conductive glass.

[0012] Furthermore, the thickness of the electron transport layer is 20-40 nm, the thickness of the perovskite light-absorbing layer is 780-820 nm, and the thickness of the hole transport layer is 100-140 nm.

[0013] In a second aspect, the present invention provides a method for preparing a perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer as described in any of the preceding claims, characterized in that it includes the following steps: S1. A SnO2 colloidal solution is spin-coated onto the surface of a transparent conductive substrate and then annealed once to form an electron transport layer. S2. First, spin-coat a PbI2 precursor solution onto the surface of the electron transport layer, and then perform a second annealing treatment to form a PbI2 layer. Then, spin-coat a FAI-MACl salt solution and perform a third annealing treatment to form a FAI-MACl layer, thus forming a perovskite light-absorbing layer. S3. Spin-coat Spro-OMeTAD solution onto the surface of the perovskite light-absorbing layer to form a hole transport layer; S4. Spin-coat a 1,3-benzenedithiophenol solution onto the surface of the hole transport layer to form a 1,3-benzenedithiophenol self-assembled monolayer. S5. A back electrode layer is prepared by self-assembling a monolayer of 1,3-benzenedithiophenol to obtain a perovskite solar cell.

[0014] Furthermore, in step S1, the spin coating speed is 3000 rpm and the spin coating time is 50 s; the temperature of the first annealing treatment is 140-160℃ and the time is 20-30 min.

[0015] Furthermore, in step S2, the PbI2 precursor solution is prepared by dissolving PbI2 powder in a mixed solvent of DMF and DMSO. The spin coating speed is 2000 rpm, the spin coating time is 30 s, and the secondary annealing temperature is 60-80℃ for 1-2 min.

[0016] Furthermore, in step S2, the FAI-MACl salt solution is prepared by dissolving FAI and MACl in IPA. The spin coating speed is 1800 rpm, the spin coating time is 30 s, and the temperature of the three annealing treatments is 140-160℃, and the time is 20-40 min.

[0017] Furthermore, in step S3, the Spro-OMeTAD solution is prepared by dissolving Spiro-OMeTAD, Li-TFSI solution and 4-tBP in chlorobenzene, and the spin coating speed is 3000 rpm and the spin coating time is 30 s.

[0018] Furthermore, in step S4, the 1,3-benzenedithiophenol solution is prepared by dissolving 1,3-benzenedithiophenol in isopropanol solution to a concentration of 0.5-2.5 mg / mL, and the spin coating speed is 3000 rpm, and the spin coating time is 30 s.

[0019] The beneficial effects of this invention are: This invention utilizes the organic molecule 1,3-benzenedithiophenol as a self-assembled monolayer to modify the interface of low-cost copper, a substitute for noble metal gold electrodes, and simultaneously modulates the Fermi level of copper. This method not only effectively suppresses copper oxidation, iodine corrosion, and bidirectional migration of metal / halogen ions, but also solves the problems of energy level mismatch, easy migration, and poor stability of pure copper electrodes. Thus, while significantly reducing the cost of electrode materials, it achieves a synergistic improvement in the high efficiency, high stability, and low cost of perovskite solar cells. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the perovskite solar cell structure of the present invention, wherein (a) is the Au top electrode device structure prepared in Comparative Example 2, (b) is the Cu top electrode device structure prepared in Comparative Example 1, and (c) is the BDT-modified Cu top electrode device structure prepared in Example 1.

[0021] Figure 2 The diagrams show the energy levels of the perovskite solar cells of the present invention, where (a) is the energy level diagram of the Au top electrode device prepared in Comparative Example 2, (b) is the energy level diagram of the Cu top electrode device prepared in Comparative Example 1, and (c) is the energy level diagram of the BDT-modified Cu top electrode device prepared in Example 1. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. It should be noted that, unless otherwise specified, all chemical reagents involved in this invention are purchased through commercial channels.

[0023] It should be noted that the specific manufacturers and models of the raw materials involved in this invention are merely examples listed to illustrate the embodiments of this invention, and should not be construed as limiting the scope of protection of this invention. The scope of protection of this invention covers all materials that meet the structural and performance requirements described, and should not be limited by the specific suppliers or product models listed in the embodiments.

[0024] 2,2',7,7'-Tetratetra[N,N-Di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD, CAS No. 207739-72-8), lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI, CAS No. 90076-65-6), 4-tert-butylpyridine (4-tBP, CAS No. 3978-81-2), formamidinium hydroiodide (FAI, CAS No. 879643-71-7), methylammonium chloride (MACl, CAS No. 593-51-1), isopropanol (IPA), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO).

[0025] 1,3-Benzenedithiophenol (BDT): CAS No. 626-04-0, purchased from Shanghai Maclean Biochemical Technology Co., Ltd., its structural formula is: ; 1,3-Benzenedithiophenol molecules contain -SH groups. When adsorbed onto the Cu surface, the -SH group loses a hydrogen atom, and the lone pair electrons on the S atom coordinate with the Cu atom, forming a Cu-S covalent bond, thereby reducing the chemical activity of the copper surface. Simultaneously, this adsorption process involves electron transfer, forming an interfacial dipole on the Cu surface, significantly lowering the Fermi level of copper and effectively eliminating the Schottky barrier between the hole transport layer and the copper electrode. Furthermore, BDT molecules are uniformly anchored to the Cu surface through the -SH group, forming a continuous and dense self-assembled organic isolation film that effectively inhibits copper oxidation, iodine corrosion, and the bidirectional migration of metal ions and halide ions, ultimately achieving energy level matching and long-lifetime stability of the copper electrode.

[0026] like Figure 1As shown in (c), the perovskite solar cell of the present invention comprises, from bottom to top, a transparent conductive substrate (ITO), a SnO2 electron transport layer, a perovskite light-absorbing layer, a hole transport layer, a 1,3-benzenedithiophenol self-assembled monolayer, and a copper electrode layer.

[0027] The above-mentioned method for preparing perovskite solar cells includes the following steps: S1. Fabrication of the electron transport layer Wipe the ITO glass substrate with a cleaning agent, then ultrasonically clean it with deionized water, acetone and isopropanol for 30 minutes in sequence, and dry it for later use. A 15 wt% SnO2 colloidal solution was diluted with deionized water at a volume ratio of 1:3, stirred at room temperature for 30 min, and then filtered to obtain a SnO2 colloidal solution. In an air atmosphere, 70 μL of SnO2 dilution was spin-coated onto the surface of an ITO substrate at a spin speed of 3000 rpm for 50 s; then annealed on a hot plate at 140-160℃ for 20-30 min to obtain a SnO2 electron transport layer with a thickness of 20-40 nm. S2. Preparation of perovskite light-absorbing layer 599.3 mg of PbI2 powder was dissolved in a mixed solvent of 950 μL DMF and 50 μL DMSO and stirred at 70 °C for 6 h to obtain a PbI2 precursor solution. Dissolve 90 mg FAI and 12 mg MACl in 1 mL IPA and stir at room temperature for 30 min to obtain FAI-MACl salt solution; Under a nitrogen atmosphere, 70 μL of PbI2 precursor solution was spin-coated onto the surface of SnO2 electron transport layer at a spin speed of 2000 rpm for 30 s. The mixture was then annealed on a hot plate at 60-80℃ for 1-2 min and allowed to cool naturally for 10 min to obtain the PbI2 layer. Next, 70 μL of FAI-MACl salt solution was spin-coated onto its surface at a spin speed of 1800 rpm for 30 s. This was followed by annealing on a hot plate at 140-160℃ for 20-40 min to obtain the FAI-MACl layer, resulting in a perovskite light-absorbing layer with a thickness of 780-820 nm. S3. Preparation of the hole transport layer Spro-OMeTAD solution was prepared by dissolving 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 ml acetonitrile) and 29 μL 4-tBP in 1 ml chlorobenzene. Under a nitrogen atmosphere, 50 μL of Spro-OMeTAD solution was spin-coated onto the surface of the perovskite light-absorbing layer at a spin-coating speed of 3000 rpm for 30 s to obtain a hole transport layer with a thickness of 100-140 nm. S4. Preparation of self-assembled monolayers Dissolve 1,3-benzenedithiophenol in isopropanol solution to prepare a 1,3-benzenedithiophenol solution with a concentration of 0.5-2.5 mg / mL; A 1,3-benzyldithiophenol solution was spin-coated onto the surface of the hole transport layer at a speed of 3000 rpm for 30 s to obtain a 1,3-benzyldithiophenol self-assembled monolayer. S5. Preparation of copper electrode layer On a self-assembled monolayer of 1,3-benzyl dithiophenol, thermal evaporation was performed at a depth of 5 × 10⁻⁶. -4 A copper electrode with a thickness of 140-160 nm is vacuum-deposited under a vacuum of Pa to obtain a copper electrode, and finally a perovskite solar cell is fabricated.

[0028] The present invention will be further illustrated by specific embodiments below.

[0029] Example 1 This embodiment provides a perovskite solar cell based on a copper electrode modified with a 1,3-benzyldithiophenol self-assembled monolayer, comprising a transparent conductive substrate, a SnO2 electron transport layer, a perovskite light-absorbing layer, a hole transport layer, a 1,3-benzyldithiophenol self-assembled monolayer, and a copper electrode layer, which are stacked sequentially from bottom to top.

[0030] This embodiment also provides a method for preparing a perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer, comprising the following steps: S1. Fabrication of the electron transport layer Wipe the ITO glass substrate with a cleaning agent, then ultrasonically clean it with deionized water, acetone and isopropanol for 30 minutes in sequence, and dry it for later use. A 15 wt% SnO2 colloidal solution was diluted with deionized water at a volume ratio of 1:3, stirred at room temperature for 30 min, and then filtered to obtain a SnO2 colloidal solution. In an air atmosphere, 70 μL of SnO2 dilution was spin-coated onto the surface of an ITO substrate at a spin speed of 3000 rpm for 50 s; then annealed on a hot plate at 1150 °C for 25 min to obtain a SnO2 electron transport layer with a thickness of 30 nm. S2. Preparation of perovskite light-absorbing layer 599.3 mg of PbI2 powder was dissolved in a mixed solvent of 950 μL DMF and 50 μL DMSO and stirred at 70 °C for 6 h to obtain a PbI2 precursor solution. Dissolve 90 mg FAI and 12 mg MACl in 1 mL IPA and stir at room temperature for 30 min to obtain FAI-MACl salt solution; Under a nitrogen atmosphere, 70 μL of PbI2 precursor solution was spin-coated onto the surface of SnO2 electron transport layer at a spin speed of 2000 rpm for 30 s. The layer was then annealed on a hot plate at 70 °C for 1 min and allowed to cool naturally for 10 min to obtain the PbI2 layer. Next, 70 μL of FAI-MACl salt solution was spin-coated onto its surface at a spin speed of 1800 rpm for 30 s. The layer was then annealed on a hot plate at 150 °C for 30 min to obtain the FAI-MACl layer, resulting in a perovskite light-absorbing layer with a thickness of 800 nm. S3. Preparation of the hole transport layer Spro-OMeTAD solution was prepared by dissolving 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 ml acetonitrile) and 29 μL 4-tBP in 1 ml chlorobenzene. Under a nitrogen atmosphere, 50 μL of Spro-OMeTAD solution was spin-coated onto the surface of the perovskite light-absorbing layer at a spin-coating speed of 3000 rpm for 30 s to obtain a hole transport layer with a thickness of 120 nm. S4. Preparation of self-assembled monolayers Dissolve 1,3-benzyldithiophenol in isopropanol solution to prepare a 1.5 mg / mL 1,3-benzyldithiophenol solution; A 1,3-benzyldithiophenol solution was spin-coated onto the surface of the hole transport layer at a speed of 3000 rpm for 30 s to obtain a 1,3-benzyldithiophenol self-assembled monolayer. S5. Preparation of copper electrode layer On a self-assembled monolayer of 1,3-benzyl dithiophenol, thermal evaporation was performed at a depth of 5 × 10⁻⁶. -4 A copper electrode with a thickness of 150 nm was vacuum-deposited under a vacuum of Pa to obtain a copper electrode, and finally a perovskite solar cell was fabricated.

[0031] Comparative Example 1 This comparative example provides a perovskite solar cell, comprising a transparent conductive substrate, a SnO2 electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a copper electrode layer, which are stacked sequentially from bottom to top.

[0032] Compared with Example 1, the difference in this comparative example is that no 1,3-benzenedithiophenol self-assembled monolayer is provided between the hole transport layer and the copper electrode layer.

[0033] Accordingly, this comparative example also provides a method for preparing a perovskite solar cell, which differs from Example 1 only in that step S4 is omitted, while the remaining steps and process conditions are the same as in Example 1.

[0034] Comparative Example 2 This comparative example provides a perovskite solar cell, comprising a transparent conductive substrate, a SnO2 electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a gold electrode layer, which are stacked sequentially from bottom to top.

[0035] Compared with Example 1, the difference in this comparative example is that the back electrode is a gold electrode, and no 1,3-benzenedithiophenol self-assembled monolayer is provided between the hole transport layer and the gold electrode layer.

[0036] Accordingly, this comparative example also provides a method for preparing a perovskite solar cell, which differs from Example 1 only in that step S4 is omitted, and in step S5, gold is deposited as the back electrode by vacuum evaporation with a deposition thickness of 80 nm.

[0037] Figure 1 The diagram shows a comparison of the three-dimensional layered structures of the three sets of nip-type perovskite solar cells of the present invention. The three sets of devices all adopt the same functional layer stacking structure from bottom to top, namely: ITO transparent conductive substrate, SnO2 electron transport layer, perovskite light-absorbing layer and Spiro-OMeTAD hole transport layer; wherein, Figure (a) is a conventional Au top electrode control device, Figure (b) is a pure Cu top electrode device without modification layer, and Figure (c) is the device designed in the present invention, which uses low-cost copper to replace the precious metal gold as the top electrode, and introduces a BDT self-assembled monolayer between the Spiro-OMeTAD hole transport layer and the Cu electrode. By adding this modification layer, a novel composite electrode structure is constructed.

[0038] Figure 2 The diagram shows a comparison of the energy level arrangements of three sets of nip perovskite solar cells with different top electrode structures. The device in Figure (c) of this invention innovatively introduces a BDT self-assembled monolayer modification between the Cu electrode and the Spiro-OMeTAD hole transport layer to construct a Cu / BDT composite top electrode structure. Compared with Au electrodes, it is cheaper, and the energy level of the composite electrode can be tuned to -5.14 eV. Compared with the pure Cu electrode, it is more matched to the energy level of Spiro-OMeTAD (-5.20 eV), effectively reducing the interface energy level barrier and optimizing the hole extraction and transport characteristics. This clearly demonstrates the energy level matching and control of the low-cost copper electrode modified with BDT.

[0039] Figure 2 This diagram illustrates the energy level arrangement comparison of three sets of nip-type perovskite solar cells with different top electrode structures according to the present invention. Figure (c) shows the device structure designed in this invention, which introduces a BDT self-assembled monolayer between the Cu electrode and the Spiro-OMeTAD hole transport layer for interface modification, constructing a Cu / BDT composite top electrode structure. The energy level of this composite electrode is tuned to -5.14 eV, which is closer to the energy level of Spiro-OMeTAD (-5.20 eV) than that of the pure Cu electrode. This effectively reduces the interface energy level barrier and optimizes the hole extraction and transport characteristics. At the same time, this structure uses low-cost copper instead of precious metal gold as the electrode material, which significantly reduces the material cost while ensuring energy level matching. This directly demonstrates the role of BDT modification in the energy level matching and regulation of low-cost copper electrodes.

[0040] Photovoltaic performance testing Under the test conditions (one solar irradiance), the photovoltaic performance of Cu / BDT devices modified with different concentrations of BDT (BDT concentrations of 0.5, 1.0, 1.5, 2.0, and 2.5 mg / mL) and Comparative Examples 1 and 2 were tested using a solar simulator. The results are shown in Table 1.

[0041] Table 1 Photovoltaic performance parameters of different devices As shown in Table 1, the photoelectric conversion efficiency of the pure Cu electrode device is only 20.6%, significantly lower than that of the Au electrode device (24.2%). After BDT modification, the performance of the Cu / BDT device is significantly improved. At the optimal BDT concentration (1.5 mg / mL), the photoelectric conversion efficiency of the device reaches 24.23%, comparable to that of the Au electrode device. Furthermore, the BDT concentration has a significant impact on device performance; when the concentration is too low (0.5 mg / mL) or too high (2.5 mg / mL), the interface modification effect weakens, and the device efficiency decreases accordingly.

[0042] The above results indicate that by introducing a 1,3-benzyldithiophenol self-assembled monolayer between the Cu electrode and the hole transport layer for interface modification, the present invention can effectively control the Fermi level of copper, eliminate the Schottky barrier between the hole transport layer and the copper electrode, and suppress copper oxidation and ion migration. Thus, while significantly reducing electrode costs, it achieves photoelectric conversion efficiency comparable to that of noble metal Au electrodes, significantly improving the performance of PSCs.

[0043] The present invention and its embodiments have been described above. This description is not restrictive, and the embodiments shown are only one of the embodiments of the present invention. The actual structure is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar structures and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer, characterized in that, It includes a transparent conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a back electrode layer stacked sequentially from bottom to top. A 1,3-benzenedithiophenol self-assembled monolayer is also disposed between the hole transport layer and the back electrode layer.

2. The perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 1, characterized in that, The back electrode is a copper electrode, and the thickness of the back electrode layer is 140-160 nm.

3. A perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 1, characterized in that, The perovskite light-absorbing layer comprises a PbI2 layer and a FAI-MACl layer stacked sequentially from bottom to top.

4. A perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 1, characterized in that, The transparent conductive substrate is indium tin oxide conductive glass.

5. A perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 1, characterized in that, The electron transport layer has a thickness of 20-40 nm, the perovskite light-absorbing layer has a thickness of 780-820 nm, and the hole transport layer has a thickness of 100-140 nm.

6. A method for preparing a perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer, as described in any one of claims 1-5, characterized in that... Includes the following steps: S1. A SnO2 colloidal solution is spin-coated onto the surface of a transparent conductive substrate and then annealed once to form an electron transport layer. S2. First, spin-coat a PbI2 precursor solution onto the surface of the electron transport layer, and then perform a second annealing treatment to form a PbI2 layer. Then, spin-coat a FAI-MACl salt solution and perform a third annealing treatment to form a FAI-MACl layer, thus forming a perovskite light-absorbing layer. S3. Spin-coat Spro-OMeTAD solution onto the surface of the perovskite light-absorbing layer to form a hole transport layer; S4. Spin-coat a 1,3-benzenedithiophenol solution onto the surface of the hole transport layer to form a 1,3-benzenedithiophenol self-assembled monolayer. S5. A back electrode layer is prepared by self-assembling a monolayer of 1,3-benzenedithiophenol to obtain a perovskite solar cell.

7. The method for preparing a perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 6, characterized in that, In step S2, the PbI2 precursor solution is prepared by dissolving PbI2 powder in a mixed solvent of DMF and DMSO. The spin coating speed is 2000 rpm, the spin coating time is 30 s, and the secondary annealing temperature is 60-80℃ for 1-2 min.

8. The method for preparing a perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 6, characterized in that, In step S2, the FAI-MACl salt solution is prepared by dissolving FAI and MACl in IPA. The spin coating speed is 1800 rpm and the spin coating time is 30 s. The temperature of the three annealing treatments is 140-160℃ and the time is 20-40 min.

9. The method for preparing a perovskite solar cell based on a copper electrode modified with a 1,3-benzenedithiophenol self-assembled monolayer according to claim 6, characterized in that, In step S3, the Spro-OMeTAD solution was prepared by dissolving Spiro-OMeTAD, Li-TFSI solution and 4-tBP in chlorobenzene. The spin coating speed was 3000 rpm and the spin coating time was 30 s.

10. The method for preparing a perovskite solar cell based on a 1,3-benzenedithiophenol self-assembled monolayer modified copper electrode according to claim 6, characterized in that, In step S4, the 1,3-benzenedithiophenol solution is prepared by dissolving 1,3-benzenedithiophenol in isopropanol solution to a concentration of 0.5-2.5 mg / mL. The spin coating speed is 3000 rpm and the spin coating time is 30 s.